2014
DOI: 10.1007/s11164-014-1865-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of biomorphic Ni–Al LDHs using cotton from discarded T–shirt as a template and the adsorption capability for Congo red

Abstract: Biomorphic Ni-Al layered double-hydroxide (LDH) nanosheets with 3D hierarchical structures were synthesized with cotton from discarded T-shirt as templates. The as-prepared samples were characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, thermogravimetry-differential thermal analysis, scanning electron microscopy, and energy-dispersive X-ray diffraction. Adsorption of Congo red (CR) by calcined Ni-Al layered double hydroxides (CLDH) from aqueous solution was investigated in detail. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The method is considered particularly attractive owing to the low cost, renewable nature, biodegradable character, and environmental compatibility of natural reagents. A literature search shows that synthesis of Ht with the use of sacrificial biotemplates is a very recent tendency, with research concentrating so far on the hard templating syntheses, in which the nanostructure of rigid biomaterials was replicated in the final Ht product [10][11][12][13][14][15][16][17][18][19]. In most works cellulosic polymers of various provenience have been used in the capacity of sacrificial biotemplates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is considered particularly attractive owing to the low cost, renewable nature, biodegradable character, and environmental compatibility of natural reagents. A literature search shows that synthesis of Ht with the use of sacrificial biotemplates is a very recent tendency, with research concentrating so far on the hard templating syntheses, in which the nanostructure of rigid biomaterials was replicated in the final Ht product [10][11][12][13][14][15][16][17][18][19]. In most works cellulosic polymers of various provenience have been used in the capacity of sacrificial biotemplates.…”
Section: Introductionmentioning
confidence: 99%
“…In most works cellulosic polymers of various provenience have been used in the capacity of sacrificial biotemplates. In such a way formation of biomorphic hierarchical Mg-Al, Zn-Al and Ni-Al Ht was achieved, the materials proving to be excellent adsorbents of a variety of substances, including bovine serum albumin, oil, dyes and antibiotics [11,[13][14][15][16]18]. Zhang et al [12] demonstrated that advanced Zn-Al Ht/Al 2 O 3 composites with tunable compositions and micro/nanostructures could be grown by structure replication of cellulose fibers.…”
Section: Introductionmentioning
confidence: 99%